The meaning of space in Islamic housing in Bogor (ARTEKS : Jurnal Teknik Arsitektur, 2026)
The phenomenon of housing based on Islamic values is increasingly developing in Indonesia, yet research on the spatial manifestations of these values and local culture remains limited. This study aims to analyze how the Islamic values embraced by Muhammadiyah and the Indonesian Da'wah Institute (LDII) are realized in the production of residential space in Bogor, employing Henri Lefebvre's theoretical framework. Through a comparative analysis of Mustika Residence Muhammadiyah and the Nurul Iman Mosque Complex of LDII, this research reveals significant differences across the three dimensions of space production. Muhammadiyah housing exhibits moderate spatial practices with functional design and symbols of Islamic renewal, while LDII housing displays clear physical boundaries and dominant internal interactions. The implications of this research for the field of architecture highlight the importance of considering religious values and local culture in residential space design. These findings can assist stakeholders in creating housing that is responsive to community needs and provide insights for academics and practitioners. This study enriches Lefebvre's theory by demonstrating the role of religious dimensions in space formation, proving that variations in interpretation within a single value system can lead to different spatial manifestations, thereby contributing to interdisciplinary studies on religion and urban space.
Keywords: Islamic housing; Islamic value; LDII; Muhammadiyah; Spatial practice; Spatial production; Spatial representation; Representational space